ANÁLISE DA EVOLUÇÃO DO EMPREGO FORMAL DO MUNICIPIO DE IJUÍ - Arruda, Jônatas; Pacheco, Jussiano R.; Lucca, Emerson J.; Kohler, Romualdo; Trennepoh, Dilson; Schiavo, Andressa (Salão do Conhecimento, 2013)
Resumo